VERBALIZATION OF THE NATIVE LAND CONCEPT IN OLEKSII DOVHIY’S POETRY - Strokal , Oleksandr (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article deals with the peculiarities of the linguistic expression of the NATIVE LAND concept in Oleksii Dovhiy’s poetry. The study found that the current stage of linguistics is characterized by an understanding of the concept as a general concept and complex of culturally determined perceptions of the subject. The concept itself is a designated element of the ideal that represents the reality of the speaker through the prism of his culture. The article argues that the individual’s ideas about the subject are realized in the artistic text through a figurative system. The image is considered as the main means of artistic generalization of reality, as a sign of the objective correlate of human experiences and as a special form of social consciousness. In Oleksii Dovhiy’s poetic texts the image of the native land is one of the most vividly presented. For the poet’s lyrical hero, this image serves as a special place, a sacred locus, the beginning of all things. This vision of the lyrical hero is expressed in the nominations for the designation of landscape elements, natural phenomena and their characteristics. Supplements the analyzed locus introduced by the author image of the Big Father, expressed by the respective linguistic units. The author’s poetic language presents linguistic constructions that explicate the image of the native land as the beginning of all things a place in which the memory of the heroic past and the difficult tests are stored at the same time. ________________ References: • Holubovska, O., Koroliov, I. R. Aktual’ni problemy suchasnoji linhvistyky: kurs lektsii [Topical problems of modern linguistics] (Kyiv, Vydavnuch-polihrafochnyi tsentr «Kyivskyi Universytet», 2011), 223 (in Ukr.). • Vezhbickaja, A. Ponimanie kul’tur cherez posredstvo kljuchevyh slov [Understanding cultures through keywords] (Moscow, 2001), 288 (in Russ.). • Moskvychova, O. A. «Poetychnyj tekst jak specyfichnyj zasib vidtvorennja dijsnosti [Poetic text as a specific means of reproducing reality].» Studia linguistica 13 (2018): 215-227 (in Ukr.). • Dovgyj, P. «Dotorky blyskavky [Lightning touches].» Vybrani tvory v chotyr’oh tomah (Kyiv, Ukr. pys’mennyk, 1, 2009), 414 (in Ukr.). • Dovgyj, P. «Dyhannja vichnosti. Vos’myvirshi [The breath of eternity. Octopus].» Vybrani tvory v chotyr’oh tomah (Kyiv, Ukr. pys’mennyk, 2, 2009), 388 (in Ukr.). • Dovgyj, P. «Derevoryty.» Vybrani tvory v chotyr’oh tomah (Kyiv, Ukr. pys’mennyk, 3, 2009), 536 (in Ukr.).